Do Data Centres Create Jobs? Comparing Digital Infrastructure, Manufacturing, and Tourism in Batam, Indonesia - Gracia Billy Mambrasar (International Journal of Social Service and Research, 2026)
Batam, Indonesia, has grown into a regional digital infrastructure hub, particularly through the development of data centers in Nongsa and other investment promotion initiatives. This article examines whether data center investment in Batam can reduce unemployment to the same extent as manufacturing and tourism sectors. Through a comparative documentary analysis, this study draws on Batam’s official labor market profiles, investment announcements, policy reports, and literature related to data centers, manufacturing, tourism, and employment multipliers. The results show that Batam’s labor market challenges are broad-based and primarily related to medium-skilled employment. In 2025, Batam recorded 49,931 unemployed individuals and 29,710 job seekers, with most job seekers being senior secondary education graduates. In contrast, large-scale data center projects require substantial investment but generate relatively limited direct employment opportunities. For example, a US$5 billion AI data center project in Nongsa is projected to create only 700–800 professional jobs in 2025, representing approximately 1.4%–1.6% of Batam’s unemployed population. Data centers, therefore, are expected to play an important role in long-term digital transformation, infrastructure development, and the creation of high-skilled employment; however, they are unlikely to become the primary driver of short-term employment growth. Manufacturing and tourism remain more viable short- and medium-term employment sectors because they are better aligned with Batam’s labor market structure and can generate broader direct, indirect, and induced employment opportunities. This article concludes that Batam should pursue a layered development strategy that integrates digital infrastructure investment with labor-intensive and service-oriented economic sectors.